EVALUASI KUALITAS INSTRUMEN PENGUKURAN KINERJA TENAGA PENDIDIK - Uswatun Hasanah; Susilahudin Putrawangsa; Raden Fanny Printi Ardi (Jurnal Tatsqif, 2017)
The current research is an analysis on the quality of an instrument that is used to measure educator performance at a college in West Nusa Tenggara. The research aims to improve the quality of the instrument. Factor Analysis is used in the study. There are 3 measurement factors in the instrument, those are pedagogic factors (5 indicators), professionalism (11 indicators) and personality (3 indicators). The result shows that: 1) those indicators can be classified into two factors, formal factors and informal factors. Formal factors is institutional and structured, such as the indicators of subject matter delivery, the use of teaching method, the use of relevance example, and the use of learning media and tools. Meanwhile, informal factors is non-institutional, which tends to be emotional relationship or informal relationship, such as educators capability in creating pleasant and friendly classroom; 2) It is found that some indicators need to be removed because they have indicator values less than 0.5, for instance the indicator that ‘lecturers explain the relationship between the subjects being taught and other subjects outside that subjects’ is need to be removed because it has a similar meaning with another indicator that is ‘lectures explain the application of the subject in real life’.